Sodium-Glucose Cotransporter 2 Inhibitors Mechanisms of Action: A Review - Fonseca-Correa, Jorge I.; Correa-Rotter, Ricardo (Frontiers in Medicine, 2021)
Sodium-Glucose Cotransporter 2 inhibitors (SGLT2i), or gliflozins, are a group of antidiabetic drugs that have shown improvement in renal and cardiovascular outcomes in patients with kidney disease, with and without diabetes. In this review, we will describe the different proposed mechanisms of action of SGLT2i. Gliflozins inhibit renal glucose reabsorption by blocking the SGLT2 cotransporters in the proximal tubules and causing glucosuria. This reduces glycemia and lowers HbA1c by approximately 1.0%. The accompanying sodium excretion reverts the tubuloglomerular feedback and reduces intraglomerular pressure, which is central to the nephroprotective effects of SGLT2i. The caloric loss reduces weight, increases insulin sensitivity, lipid metabolism, and likely reduces lipotoxicity. Metabolism shifts towards gluconeogenesis and ketogenesis, thought to be protective for the heart and kidneys. Additionally, there is evidence of a reduction in tubular cell glucotoxicity through reduced mitochondrial dysfunction and inflammation. SGLT2i likely reduce kidney hypoxia by reducing tubular energy and oxygen demand. SGLT2i improve blood pressure through a negative sodium and water balance and possibly by inhibiting the sympathetic nervous system. These changes contribute to the improvement of cardiovascular function and are thought to be central in the cardiovascular benefits of SGLT2i. Gliflozins also reduce hepcidin levels, improving erythropoiesis and anemia. Finally, other possible mechanisms include a reduction in inflammatory markers, fibrosis, podocyte injury, and other related mechanisms. SGLT2i have shown significant and highly consistent benefits in renal and cardiovascular protection. The complexity and interconnectedness of the primary and secondary mechanisms of action make them a most interesting and exciting pharmacologic group.